#PlasticFreeJuly – Analyzing a Worldwide Campaign to Reduce Single-use Plastic Consumption with Twitter. Issue 7 (3rd October 2021) - Heidbreder, Lea Marie; Lange, Martin; Reese, Gerhard
ABSTRACT: Plastic pollution is ubiquitous in the environment. One initiative that tackles this global environmental problem is the "Plastic Free July, " a worldwide campaign encouraging consumers to reduce their single-use plastic consumption during the month of July. In the current study, we investigate microblogging in order to analyze the messages people spread within the scope of the campaign. This paper presents results of a Twitter analysis based on data from July 2018, assessing 16, 363 tweets linked to the hashtag #plasticfreejuly. User structure shows that private individuals and shops frequently used this hashtag. Simultaneously, a content analysis reveals that consumption patterns mentioned in the tweets refer not only to boycott (e.g. avoidance of plastic straws) but also to buycott (e.g. praising reusable coffee cups) as forms of political consumption. The three R's of waste management – reduce, reuse, recycle – were frequently mentioned in the tweets. Thus, the empowerment of consumers was promoted by solution-based rather than problem-based communication.